An Innovative Guided Inquiry Worksheet Integrated with the Nested Approach to Enhance Students’ Critical Thinking Skills in Chemical Equilibrium - Favian Agung Difa' Saskara; Bertha Yonata (Postgraduate, University of Mataram, 2025)
This study aims to describe the feasibility of a guided inquiry-based worksheet integrated with a nested approach to train students' critical thinking skills in chemical equilibrium material. The feasibility of the worksheet is assessed from the aspects of validity, practicality, and effectiveness. The research method used is Research and Development (R&D), which uses the 4D development model by Thiagarajan (1974), which is limited to the stages of defining, designing, and developing. A limited trial was conducted in April 2025 on 29 high school students in Surabaya. The results of the study showed that the validity of the worksheet was included in the valid category with a median validity score of 5. The practicality of the worksheet was assessed as practical based on student responses (96.17%), and observation sheets ≥ 61% of student activities were relevant. The effectiveness of the worksheet was proven to be high, as indicated by the N-Gain analysis of the critical thinking skills test, which showed a high category. Based on these findings, it can be concluded that the guided inquiry-based worksheet integrated with a suitable approach for chemical equilibrium learning is suitable for use to improve student's critical thinking skills.